Understanding and Managing Job Stress in the Service Sector: A Literature Review - Yusriani, Sri; Nurbaeti, Nunung; Patiro, Shine Pintor Siolemba (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
Job stress is an integral aspect of human resource development dynamics within organizations. This literature review investigates job stress, highlighting its prevalence as a critical issue for employees in various service sectors, such as healthcare, hospitality, banking, consumer, and courier services. The study sets out to accomplish two primary goals: firstly, to delineate the factors that contribute to job stress, and secondly, to evaluate the repercussions of job stress on employees. By examining insights from ten prior studies, we identify a comprehensive array of internal and external factors that intensify job stress. We further explore the influence of these stressors on vital outcomes, including turnover intentions, employee performance, and burnout. Our findings reveal that job stress significantly impacts employees' intentions to leave. Nonetheless, effectively managing job stress can foster positive outcomes for organizations. These insights underscore the critical need for management in the service sector to grasp the complex origins of job stress fully. Armed with this understanding, they can devise and implement strategies to reduce turnover intentions, bolstering overall organizational performance